2006
DOI: 10.1152/ajpheart.00400.2006
|View full text |Cite
|
Sign up to set email alerts
|

Progressive epicardial coronary blood flow reduction fails to produce ST-segment depression at normal heart rates

Abstract: ST-segment depression is commonly seen in patients with acute coronary syndromes. Most authors have attributed it to transient reductions in coronary blood flow due to nonocclusive thrombus formation on a disrupted atherosclerotic plaque and dynamic focal vasospasm at the site of coronary artery stenosis. However, ST-segment depression was never reproduced in classic animal models of coronary stenosis without the presence of tachycardia. We hypothesized that ST-segment depression occurring during acute coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Animal studies directly measuring myocardial perfusion during acute ischemia have also confirmed the insensitivity of the ECG to detect ischemia that is restricted to the subendocardium. de Chantal et al (7) found no electrocardiographic evidence of ischemia in swine when subendocardial perfusion was reduced by up to 50% by an acute partial LAD occlusion. Collectively, the findings in humans and animal models of acute ischemia support the notion that electrocardiographically silent myocardial ischemia is common and could explain the development of extensive intrinsic adaptations of the myocardium to chronic repetitive ischemia in the absence of ST segment changes in swine with hibernating myocardium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Animal studies directly measuring myocardial perfusion during acute ischemia have also confirmed the insensitivity of the ECG to detect ischemia that is restricted to the subendocardium. de Chantal et al (7) found no electrocardiographic evidence of ischemia in swine when subendocardial perfusion was reduced by up to 50% by an acute partial LAD occlusion. Collectively, the findings in humans and animal models of acute ischemia support the notion that electrocardiographically silent myocardial ischemia is common and could explain the development of extensive intrinsic adaptations of the myocardium to chronic repetitive ischemia in the absence of ST segment changes in swine with hibernating myocardium.…”
Section: Discussionmentioning
confidence: 97%
“…Since the ECG may be relatively insensitive to detect subtle degrees of subendocardial ischemia (7), hemodynamic indexes such as LV end-diastolic pressure (LVEDP) or indexes of LV contractility might provide more sensitive indicators of ischemia since they change quickly after total coronary occlusion (27) and before the development of ST segment changes or angina in patients (5). We therefore performed the present study to determine if LV hemodynamic variables at the onset of a spontaneous episode of VT/VF in swine with hibernating myocardium differ from animals that survive.…”
mentioning
confidence: 99%
“…One reason for the uncertainty is the difficulty of reproducing it in animal models at normal heart rate [8,28,29]. Understanding of subendocardial ischemia therefore depends on careful analysis of the limited data that can be obtained from patients, and on computer modeling.…”
Section: Introductionmentioning
confidence: 99%